THE TAX ON PROFESSIONAL INCOME: WHAT IS IT – DECODING THE ABBREVIATION OF THE NAP, A LIST OF PROFESSIONS - Amonova Dilshoda Suxrobovna (INTERNATIONAL JOURNAL OF SOCIAL SCIENCE & INTERDISCIPLINARY RESEARCH ISSN: 2277-3630 Impact factor: 8.036, 2024)
Today, a special type of taxation designed for the self-employed has come into focus. Consider the Professional Income Tax (NAP): what it is, what it gives, who it suits, what limitations it implies, how to use it correctly, and other points. As many details as possible so that you can put him at your service.